Engineering design process - Haik, Yousef (Longman, 2018)
Readers gain a clear understanding of engineering design as ENGINEERING DESIGN PROCESS, 3E outlines the process into five basic stages -- requirements, product concept, solution concept, embodiment design and detailed design. Designers discover how these five stages can be seamlessly integrated. The book illustrates how the design methods can work together coherently, while the book’s supporting exercises and labs help learners navigate the design process. The text leads the beginner designer from the basics of design with very simple tasks -- the first lab involves designing a sandwich -- all the way through more complex design needs. This effective approach to the design model equips learners with the skills to apply engineering design concepts both to conventional engineering problems as well as other design problems.